PARTISIPASI TOKOH ADAT SEBAGAI STRATEGI PENGAWASAN BAWASLU KOTA PALANGKA RAYA DALAM PEMILIHAN KEPALA DAERAH DAN PEMILU DI KOTA PALANGKA RAYA: The Involvement of Traditional Leaders as a Supervision Strategy of the Palangka Raya City Election Supervisory Agency in the Regional Head Elections and General Elections in Palangka Raya City - Winarno, Edi; Negara, Danes Jaya; Harinie, Luluk Tri (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2023)
This research aims to understand the strategies employed by the Election Supervisory Board (Bawaslu) of Palangka Raya City in increasing community participation, particularly among indigenous leaders, in the 2020 regional head elections and preparation for the 2024 general elections, as well as efforts to improve Bawaslu’s supervision strategies for the 2024 elections. A descriptive research method with a qualitative approach was used to generate systematic, factual, and accurate data. The results show that Bawaslu of Palangka Raya City has four main strategies to increase community participation in regional head and general elections, namely collaboration with universities and organizations, socialization through banners and brochures, and the use of social media. Although these strategies received positive responses from indigenous leaders, involving more indigenous, religious, and community leaders in every supervision activity by Bawaslu of Palangka Raya City is necessary.